(2+х)(16+х)=11×4
х²+18х+32-44=0
х²+18х-12=0
D = b²-4ac = 18²-4×1×(-12) = 372
x=(-18+√372)/2 или х=(-18-√372)/2
х=(-18+2√93)/2 или х=(-18+2√93)/2
х=2×(-9+√93)/2 или х=2×(-9-√93)/2
х=-9+√93 или х=-9-√93.
|x - 4| * (2x + 7) = 0
Приравняем к нулю оба множителя:
|x - 4| = 0
2x + 7 = 0
Решим каждый:
|x - 4| = 0
x - 4 = 0
x = 4
2x + 7 = 0
2x = -7
x = - 7 : 2
x = -3.5
ответ: -3,5; 4
|x + 1,7| * (2x + 3) = 0
Приравняем к нулю оба множителя:
|x + 1,7| = 0
2x + 3 = 0
Решим каждый:
|x + 1,7| = 0
x + 1.7 = 0
x = -1.7
2x + 3 = 0
2x = -3
x = -3 : 2
x = -1,5
ответ: -1,5; -1,7
|5x - 8| * (x - 6) = 0
Приравняем к нулю оба множителя:
|5x - 8| = 0
x - 6 = 0
Решим каждый:
|5x - 8| = 0
5x - 8 = 0
5x = 8
x = 8 : 5
x = 1.6
x - 6 = 0
x = 6
ответ: 1,6; 6
x=-9±√93
Пошаговое объяснение:
√372=2√93
x=(-18±2√93)/2
x=-9±√93